Streptococcus pneumoniae carriage, serotypes, genotypes, and antimicrobial resistance trends among children in Portugal, after introduction of PCV13 in National Immunization Program - Candeias, Catarina (2024)
Funding Information: This work was supported by unrestricted research grant from Pfizer (to RSL), and through MOSTMICRO (LISBOA-01-0145-FEDER-007660) funded by FEDER through COMPETE2020 \u2013 Programa Operacional Competitividade e Internacionaliza\u00E7\u00E3o (POCI) . CC and BF were supported by grants PD/BD/148434/2019 and 2020.05293.BD, respectively. Publisher Copyright: © 2024 The Authors